Sustainability and the Environmental Kuznets Curve Conjecture - Hamaide, Bertrand (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on empirical analyses of the Environmental Kuznets Curve. Most papers apply their research on CO2 emissions. The papers in this Special Issue seek to improve modeling techniques to prevent econometrical flaws (e.g., by adding additional explanatory variables and/or moving away from linear regression models) and apply their models to specific countries or groups of countries.